Motivation and Nurses' Fulfillment of Critical Patients' Family Needs in the Intensive Care Unit - Husain, Fida'; Imamah, Ida Nur; Mustika, Yuli; Astuti, Nining Puji; Inovasi, Monica (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: Family members may experience physical and psychological side effects, such as poor hygiene, sleep disturbances, appetite loss, anxiety, sadness, and post-traumatic stress disorder (PTSD), if they are around critically ill patients who were treated in intensive care units. Ensuring family needs are met during patients' stays in the intensive care unit can help to lessen the negative impacts. Objective: The aim of this study is to determine whether nurse motivation and meeting the needs of their critically sick patients' families are related. Methods: The type of research is quantitative, descriptive correlational to determine the relationship between nurse motivation and meeting the needs of families of critical patients. The population in this study were all ICU nurses at One of Public Hospital in Salatiga, totaling 32 people using total sampling technique. Results: The results of this study indicate that the intensive care nurses in the ICU is in the good category in nurse motivation (53,3%), also family needs fulfillment in good category (50%). Meeting the needs of the families of critically ill patients in the intensive care unit is correlated with nurse motivation (p value < 0,000). Conclusion: As a support system for the patient's recovery and to mitigate any negative effects on the family, nurses must attend to the needs of the critical patient's family.